Can Corporate Social Responsibility Turn an Asset into A Profit Boosting? - Oki Dewa Brata, Ignatius; Gusnandar Arnan, Sendi; Novira Hartiandini, Dania (International Journal of Psychosocial Rehabilitation, 2020)
This research aims to determine how much corporate social responsibility affects the level of profitability of companies in the manufacturing industry sector listed on the Indonesia Stock Exchange in the period 2014-2019. This research is motivated by the existence of companies that refuse to carry out CSR programs because they are considered able to reduce revenue profit because it will add to the company's heavy burden. The research method used in this research is the explanatory method. This research uses a sample of manufacturing industry companies in the Indonesia Stock Exchange in the 2014-2019 period, while the data analysis used in this research is the classic assumption test, simple linear regression analysis, and hypothesis testing. The results showed that the implementation of corporate social responsibility affects the profitability of companies in the manufacturing industry sector. The more CSR indicators implemented, the higher the company's profitability.